2017
DOI: 10.1186/s13148-017-0395-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between Alu hypomethylation and severity of type 2 diabetes mellitus

Abstract: BackgroundCellular senescence due to genomic instability is believed to be one of the mechanisms causing health problems in diabetes mellitus (DM). Low methylation levels of Alu elements or Alu hypomethylation, an epigenomic event causing genomic instability, were commonly found in aging people and patients with aging phenotypes, such as osteoporosis.ResultsWe investigate Alu methylation levels of white blood cells of type 2 DM, pre-DM, and control. The DM group possess the lowest Alu methylation (P < 0.001, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
7
38
0
Order By: Relevance
“…This result is similar to a previous study demonstrating the positive correlation between the history of catch up growth and increased Alu methylation [28]. In addition, the correlation between reduced Alu methylation levels and increased quantity of DNA lesions explained why individuals with Alu hypomethylation exhibit an increased risk of disabilities related to aging, such as osteoporosis and diabetes-related hypertension [29,30]. Cells with a normal p53 function can recognize DNA damage and consequently halt cell proliferation [48][49][50][51].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This result is similar to a previous study demonstrating the positive correlation between the history of catch up growth and increased Alu methylation [28]. In addition, the correlation between reduced Alu methylation levels and increased quantity of DNA lesions explained why individuals with Alu hypomethylation exhibit an increased risk of disabilities related to aging, such as osteoporosis and diabetes-related hypertension [29,30]. Cells with a normal p53 function can recognize DNA damage and consequently halt cell proliferation [48][49][50][51].…”
Section: Discussionsupporting
confidence: 79%
“…In younger individuals, Alu methylation is directly correlated with growth rate [28]. Alu hypomethylation is associated with the severity of conditions involved in the deterioration of human health with age, such as osteoporosis [29] and diabetes mellitus [30].…”
mentioning
confidence: 99%
“…Human RIND-EDSBs are localized within hypermethylated regions (7). Genomewide hypomethylation, a common epigenomic change in aging human cells, causes several health problems such as osteoporosis and hypertension in diabetes mellitus patients (2,(43)(44)(45). Genome-wide hypomethylation is also a common epigenomic change in cancer (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported an age-dependent decline in genomic DNA methylation, both in global DNA and in Alu elements [13,14,17]. DNA Alu hypomethylation may promote an enhanced retrotransposon activity and genomic instability [12] and is associated with the severity of some age-related diseases [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Alu hypomethylation has been found during aging [13] and it has been associated with the severity of age-related diseases such as diabetes [14], cancer [15], osteoporosis [16] and cardiovascular diseases [17]. Interestingly, hypomethylation and epigenetic age are delayed in centenarians' offspring [18,19], which are considered an optimal model to study biomarkers associated with human longevity.…”
Section: Introductionmentioning
confidence: 99%